(untitled) (Research, Society and Development, 2022)
The oil/gas, ethanol, biodiesel and biogas industries generate wastewater known as produced water, vinasse, crude glycerin and methanogenic digester´s based effluents, respectively. Microalgal systems have been suggested as a suitable and adaptable biological approach for the treatment of such wastewaters. The advantage of such an approach is the combination of treatment with the accumulation of algal valuable bioproducts. This systematic literature review aims to analyze scientific and patent production with bibliometric analysis. Another aim is to discuss the algal bioremediation strategies that were adopted by the cited industries for treating their distinct effluents. Data was obtained using scientific papers and patents published between 2000 to 2020 (335 scientific papers and 104 patents). The United States contributed with the largest number of articles, followed by China and Brazil. Meanwhile China, South Korea and the United States are the major owners of patents. This work identified that microalgal based system is successful in bioremediating several pollutants and that glycerol significantly improves algal performance for bioproducts production. Nonetheless, the efficiency of this process is hindered either by the adopted strategy applied before the cultivation stage or after this process. For instance, variables such as nutrient supplementation, turbidity and salinity corrections were identified as pivotal for process performance. Thus, the full-scale process is directly associated to the correct integration of wastewater production and proper management of microalgae systems.